+0  
 
0
73
1
avatar+96 

Solve the equation: -3(-x + 5) + 20 = -10(x - 3) + 4

Olpers  Aug 25, 2018
 #1
avatar+348 
+2

First we can expand \(-3(-x + 5)\) and \(-10(x-3)\). By doing this, we get \(3x - 15 + 20 = -10x + 30 + 4\). Then, we can get \(3x +5 = -10x + 34\). After this, we need to isolate the variable; \(13x = 29\). From here, we can get \(x = \frac{29}{13}\) or \(x = 2\frac{3}{13}\)‚Äč.

 

- Daisy

dierdurst  Aug 25, 2018

18 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.